Emotional Intelligence and Its Relationship to Self Effectiveness A Field Study among a Sample of Students from The Faculty of Education - Tishreen University - Sobh, Safaa; jdeed, Lubna; al Chanta, Zainab (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to identify both the level of emotional intelligence, and self effectiveness among students of the faculty of education at the Tishreen university, and the correlation between them, as well as the study of differences in emotional intelligence and self effectiveness according to the variables (specialization and the school year). The research has adopted the descriptive approach, and its sample has contained (384) students of the Faculty of Education at Tishreen University. The researcher has used the emotional intelligence scale for (Bar-On)(1997), and self effectiveness scale for (Abu Ghali)(2012). Among the most important findings of the research: the existence of the average level of emotional intelligence and self effectiveness to the students of the Faculty of Education, and the presence of a positive correlation statistically significant between emotional intelligence and the self effectiveness among sample members, also differences have been appeared statistically significant in emotional intelligence and the self effectiveness which are attributed to the specialization factor in favor of psychological counseling students, and significant differences in emotional intelligence and self effectiveness attributed to the school year for the fourth year students.